Potential of Tapak Dara (Catharanthus roseus L.) as an Alternative Cancer Treatment - Aurora, Ardentia; Revi, Destia Nabela; Marlina, Henny; Farhanuddin, Jahra; Dewi, Mia Oktavia; Nurmalasari, Rika; Hidayat, Wawan; Hayati, Wulan Apriliana (Universitas Muhammadiyah Purwokerto, 2025)
Cancer is a condition characterized by abnormal and uncontrolled cell growth, is aggressive, and can cause death. In Indonesia, the number of cancer cases continues to increase every year. The latest data states that there are around 400 thousand new cases with the death rate reaching 240 thousand cases. Cancer treatments such as chemotherapy, radiotherapy, and surgery are commonly used as modern treatment therapies in cancer patients, but can cause various side effects. The Tapak Dara plant (Catharanthus roseus L.) is one of the popular cancer treatment alternatives, especially the content of alkaloid-derived compounds namely vinblastine and vincristine which have potential as anticancer agents. This review aims to review the benefits and effectiveness of tapak dara as a cancer treatment. Based on the literature review, tapak dara is proven to be effective in treating cancer as the compounds vinblastine and vincristine exhibit anticancer activity through the mechanism of inhibiting cell division. Thus, tapak dara (Catharanthus roseus L.) can be an effective alternative cancer treatment, but needs to be used under close supervision